2013
DOI: 10.2169/internalmedicine.52.0031
|View full text |Cite
|
Sign up to set email alerts
|

Acid Reflux in Patients with Coronary Artery Disease and Refractory Chest Pain

Abstract: Objective To investigate the influence of acid reflux on chest pain and ischemic events and the effects of cardiac drugs on acid reflux in patients with coronary artery disease (CAD) and refractory chest pain. Methods Simultaneous 24-hour esophageal pH monitoring and 24-hour continuous electrocardiogram (ECG) (Holter) results were obtained for 64 patients. Ischemic events and cardiac drug prescriptions were compared between the patients with and without gastroesophageal reflux disease (GERD). Patients fulfilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Various studies have reported angina suppression as the result of GERD therapy. Liu Y et al have found that two-week PPI therapy not only reduced cardiac ischemia, but also improved health-related quality of life in patients with CAD and GERD [26]. Dobrzycki and colleagues have shown that short-term PPIs therapy reduced the duration and number of ST-segment depression episodes in patients with GERD and CAD [15].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported angina suppression as the result of GERD therapy. Liu Y et al have found that two-week PPI therapy not only reduced cardiac ischemia, but also improved health-related quality of life in patients with CAD and GERD [26]. Dobrzycki and colleagues have shown that short-term PPIs therapy reduced the duration and number of ST-segment depression episodes in patients with GERD and CAD [15].…”
Section: Discussionmentioning
confidence: 99%
“…The authors also demonstrated significant improvement in ST-segment depression episodes and total ischemic burden following a 7-day course of proton pump therapy (PPI) in patients with GERD suggesting that restoring normal esophageal pH might eliminate acid-derived esophagocardiac reflex and hence myocardial ischemia [ 11 ]. Liu et al reported similar findings of longer duration and higher incidence of ischemic events in patients with CAD and gastric reflux [ 12 ]. Short course of PPI not only resulted in fewer ischemic events, but also significantly improved the general health-related quality of life of patients [ 12 ].…”
Section: Discussionmentioning
confidence: 61%
“…Liu et al reported similar findings of longer duration and higher incidence of ischemic events in patients with CAD and gastric reflux [ 12 ]. Short course of PPI not only resulted in fewer ischemic events, but also significantly improved the general health-related quality of life of patients [ 12 ]. Furthermore, Swiatowski et al demonstrated that 14 days of PPI therapy in 34 patients with GERD and CAD caused a significant increase in the amount of time before maximal ST depression occurred during exercise stress test, showing that PPI therapy has a favorable effect on cardiac reserve [ 13 ].…”
Section: Discussionmentioning
confidence: 61%
“…In our study, we also analyzed the rate of anti‐anginal drug administration in the two groups. Because we found that the combinations of CCB, antiplatelet drugs, and nitrates, and the combination of CCB, antiplatelet drugs, β‐blockers, and nitrates were more frequent in the patients with GERD and CAD in our previous study, we compared the prescription of combined CCB, antiplatelet drugs, and nitrates, and the combination of CCB, antiplatelet drugs, β‐blockers, and nitrates in this study, and obtained the same result.…”
Section: Discussionmentioning
confidence: 68%